2014
DOI: 10.5194/acp-14-8043-2014
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the regional impact of indonesian biomass burning emissions based on organic molecular tracers and chemical mass balance modeling

Abstract: Abstract. Biomass burning activities commonly occur in Southeast Asia (SEA), and are particularly intense in Indonesia during the dry seasons. The effect of biomass smoke emissions on air quality in the city state of Singapore was investigated during a haze episode in October 2006. Substantially increased levels of airborne particulate matter (PM) and associated chemical species were observed during the haze period. Specifically, the enhancement in the concentration of molecular tracers for biomass combustion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 51 publications
2
47
0
Order By: Relevance
“…Particularly, significant differences in sulfate and ammonium concentrations between the samples in Periods I and III were found in inorganic ion species. Engling et al (2014) reported that the concentrations of sulfate and ammonium in the haze periods affected by Indonesian peatland fires were much higher (sulfate: ~6.53, ammonium: ~42.9 times) than those in the non-haze days, which is consistent with our results. Due to the partial overlapping of variation ranges of sulfate (0.953-7.16 µg m -3 ) and ammonium (0.123-1.88 µg m -3 ) concentrations between the samples in Periods II and III, it is difficult to use these compounds as indicators for Indonesian peatland fires in light haze days.…”
Section: Oc and Ecsupporting
confidence: 83%
See 1 more Smart Citation
“…Particularly, significant differences in sulfate and ammonium concentrations between the samples in Periods I and III were found in inorganic ion species. Engling et al (2014) reported that the concentrations of sulfate and ammonium in the haze periods affected by Indonesian peatland fires were much higher (sulfate: ~6.53, ammonium: ~42.9 times) than those in the non-haze days, which is consistent with our results. Due to the partial overlapping of variation ranges of sulfate (0.953-7.16 µg m -3 ) and ammonium (0.123-1.88 µg m -3 ) concentrations between the samples in Periods II and III, it is difficult to use these compounds as indicators for Indonesian peatland fires in light haze days.…”
Section: Oc and Ecsupporting
confidence: 83%
“…Mannosan and galactosan are minor constituents compared to levoglucosan and are derived from the pyrolysis of hemicellulose. The isomers of levoglucosan, mannosan and galactosan are derived from hemicellulose pyrolysis products and also used as tracers for biomass burning as well as levoglucosan (e.g., Engling et al, 2014;Fujii et al, 2014a;Zhu et al, 2015). In this study, the concentrations of levoglucosan, mannosan, and galactosan in Period I were over 4.69, 4.29, and 2.95 times higher than the average of those in Period III, respectively, which show significant differences between them.…”
Section: Inorganic Ionsmentioning
confidence: 74%
“…While relative ratios of levoglucosan, mannosan, and galactosan have been used to distinguish between various types of biomass combustion emissions (Engling et al, 2014), peat-burning emissions did not exhibit consistent ratios of these species. The levoglucosan to mannosan ratio ranged widely from 27 to 160 with an average (± standard deviation) of 55 ± 41.…”
Section: Anhydrosugarsmentioning
confidence: 99%
“…While relative ratios of levoglucosan, mannosan, and galactosan have been used to distinguish between various types of biomass combustion emissions (Engling et al, 2014), peat burning emissions 20 did not exhibit consistent ratios of these species. The levoglucosan to mannosan ratio ranged widely 27- 160 with an average (± standard deviation) of 55±41.…”
Section: Anhydrosugarsmentioning
confidence: 99%